2013
DOI: 10.2298/sgs1304200j
|View full text |Cite
|
Sign up to set email alerts
|

Marginal seal evaluation of self-etch flowable composite materials

Abstract: Introduction. The biggest drawback of composite materials is polymerization contraction and the existence of microcracks, therefore the market is now offering a wide variety of new composite materials. The aim of this study was to evaluate the marginal seal using dye method of class V cavities restored with self-etching flowable composite material Vertise Flow polymerized with different light-curing techniques. Material and Methods. The study was conducted on 60 extracted intact human teeth (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…The difference in the results of the previously mentioned studies[ 16 17 ] from that of the present study could be attributed to the method of evaluation, the cavity design and the configuration factor. In these studies, Class V cavities were selected, and the sealing performance was evaluated regarding the extent of dye penetration visualized under a stereomicroscope at low-magnification (×16).…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…The difference in the results of the previously mentioned studies[ 16 17 ] from that of the present study could be attributed to the method of evaluation, the cavity design and the configuration factor. In these studies, Class V cavities were selected, and the sealing performance was evaluated regarding the extent of dye penetration visualized under a stereomicroscope at low-magnification (×16).…”
Section: Discussioncontrasting
confidence: 92%
“…In the present study, no statistically significant difference was found between the groups contradicting the results of previous studies. [ 16 17 ] In a study,[ 16 ] where microleakage of Class V cavities restored with Dyad Flow was compared with two-step total-etch and SEA systems, Dyad Flow showed greater leakage at the apical margin than the other groups that was statistically significant. The application of acid etching provided better occlusal and cervical marginal sealing than those without.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations